Formation, Stability and Self‐Assembly Behaviour of the Collagen‐Like Triple Helix Confirmation: The Role of Ser, Ala and Arg/Glu. Issue 45 (5th December 2019) - Shu, Feiyi; Dai, Chun; Wang, Haibo; Xu, Chengzhi; Wie, Benmei; Zhang, Juntao; Xu, Yuling; He, Lang; Li, Sheng
Abstract: The unique sequence of the α‐chain is the structural cornerstone of the collagen triple helix that dictates its conformation and molecular behavior. In this study, collagen‐like peptides of varying sequence characteristics were designed to elucidate the role of Ser (polar residues), Ala (non‐polar residues), and Arg/Glu (ionizable residues) in the formation, kinetics, and stability of the triple helix, and its self‐assembly behavior. We found that the introduction of other common amino acids in (Gly‐Hyp‐Pro)n results in varying degrees of decrease in the rate of formation and stability of the triple helix conformation and the self‐assembly into higher order structures. The introduction of Ser showed a maximal detrimental effect on these processes, followed by the Arg/Glu and Ala. Collagen‐like peptides with Ser could not form thermodynamically stable triple helix conformations and lost their ability to further self‐assemble. Arg/Glu promoted the self‐assembly of collagen‐like peptides, and electrostatic interactions and hydrogen bonding were key to the self‐assembly of periodic ordered structures similar to natural collagen. The hydrophobic interactions of Ala also accelerated self‐assembly to some extent, however, due to the lack of directionality of hydrophobic interactions, the formation of the long‐range ordered structure was affected negatively. Abstract : The role of Ser (polar residues), Ala (non‐polar residues), and Arg/Glu (ionizable residues) in the formation, stability and self‐assembly behavior of the collagen‐like triple helix conformation were investigated. Collagen‐like peptides with Ser could not form thermodynamically stable triple helix conformations and lost their ability to further self‐assemble. Electrostatic interactions and hydrogen bonding of Arg/Glu were considered key to the self‐assembly of periodic ordered structures. Hydrophobic interactions of Ala also accelerated self‐assembly, but the long‐range ordered structures of aggregates were challenging.